FAKTOR YANG MEMPENGARUHI PEMBERIAN ASI EKSKLUSIF PADA IBU MENYUSUI DI WILAYAH KERJA PUSKESMAS UMBAN SARI PEKANBARU - Rika Ruspita; Lisviarose Lisviarose (Jurnal Ilmu Kebidanan, 2019)
Mother's Milk is an exclusive food for babies. The purpose of the study was to determine the factors that influence the provision of exclusive breastfeeding in breastfeeding mothers in the work area of ​​the Umban Sari health center in Pekanbaru. This research method is the Cros Sectional Study Analysis using a questionnaire. The population in this study were all breastfeeding mothers who had babies aged 6-12 months totaling 121 people, the sample size in this study totaled 121 nursing mothers who had infants aged 6-12 months. Data analysis using Chi Square test. The results showed that 58.7% of mothers did not give exclusive breastfeeding, related variables where mothers who did not work with a P value of 0.043 were more at risk of 0.296 times (95% CI: 1,030-6,043) than working mothers, mothers with low family income with a P value of 0.001, there is a risk that there is no risk of 3,521 times (CI: 95% POR = (1,641-7,555) compared to mothers with high family income. Mothers with ill conditions are not at risk of 0,905 times giving food to babies other than breast milk healthy with a P value of 0.787 times (CI: 95% POR = (0.437-1.873). Suggestions are given in the form of increasing promotion or health counseling by health workers in health centers about breastfeeding procedures and superiority of breastfeeding needs to be improved, when mothers visit services the health of pregnant / breastfeeding mothers is accompanied by the family so that health workers can explain the importance of breastfeeding for babies and the impact of kele mahan from the use of breast milk substitutes such as formula milk, starch water, the etc.